Pediatric empyema: Are ultrasound characteristics at the time of intervention predictive of reintervention?. Issue 7 (3rd May 2022) - Haggie, Stuart; Selvadurai, Hiran; Gunasekera, Hasantha; Fitzgerald, Dominic A.; Lord, David; Chennapragada, Murthy S.
Abstract: Background: Parapneumonic effusions and empyema are the most frequent complication of pediatric pneumonia. Interventions include chest drain and fibrinolytics (CDF) or thoracoscopic surgery. CDF is considered less invasive, and more cost‐effective though with higher rates of reintervention. We hypothesized that sonographic pleural fluid characteristics could identify cases at increased risk of reintervention following primary CDF. Methods: A retrospective cohort of complicated pneumonia managed with primary CDF (2011−2018). Cases were reviewed using ultrasound criteria to describe pleural fluid. We analyzed the correlation between ultrasound findings and reintervention. Results: We report 129 cases with a median age of 3.8 years and 44% female. A repeat intervention occurred for 24/129 (19%) cases. The interobserver reliability was moderate for the number of septations ( κ 0.72, 95% CI [confidence interval]: 0.62−0.81), weak for the size of the largest locule ( κ 0.55, 95% CI: 0.44−0.67), and minimal for the level of echogenicity ( κ 0.24, 95% CI: 0.11−0.37), pleural thickening ( κ 0.29, 95% CI: 0.17−0.42), maximum effusion depth ( κ 0.37, 95% CI: 0.22−0.51), and radiologist's risk for reintervention ( κ 0.34, 95% CI: 0.18−0.5). A repeat intervention was not associated with any objective sonographic variable. Conclusion: We report no association between ultrasound characteristics and repeat intervention for complicated pneumonia following primary CDF treatment. There was minimal interobserver agreement in reporting ultrasound characteristics despite more objective criteria. Clinicians rely on ultrasound findings to support decisions around intervention in pediatric empyema. This study does not support relying on ultrasound to estimate the likelihood of reintervention.